Characterizing Nearshore Fish Assemblages From Intact and Altered Mangrove Shorelines in Biscayne Bay, Florida, United States - Lennon, Ellery; Sealey, Kathleen Sullivan (Frontiers in Marine Science, 2022)
Biscayne Bay is an urban bay in Southeast Florida, but the southern region of the Bay is dominated by mangroves. Mangrove wetlands provide important habitat for fish, but some regions are altered by drainage canals in southern Biscayne Bay. This study utilized a large public dataset to determine if fish formed distinct species assemblages throughout Biscayne Bay by examining fish surveyed at 12 different sites over 5 years. Six sites were in front of intact mangrove shorelines, while the other six sites were adjacent to mangrove sites altered by drainage canals or residential marinas. Cluster analyses revealed that fish did form distinct species assemblage clusters which were correlated with salinity and depth. Mangrove shoreline type (intact vs. canal-altered) and geographic location did not appear to affect species composition or diversity in fish assemblages across Southern Biscayne Bay.